Novel Atmospheric Plasma Enhanced Silk Fibroin Nanofiber/Gauze Composite Wound Dressings (Journal of Fiber Bioengineering and Informatics, 2012)
In this work, Silk Fibroin (SF) nanofibers were electrospun onto plasma-treated 100% cotton gauzebandages to form a novel silk-gauze composite wound dressing. Atmospheric pressure plasma pre- andpost-treatments were used to increase the adhesion between the SF nanofibers and cotton substrates.The adhesion of the nanofibers to the substrates was assessed by qualitative and quantitative techniques.Plasma pre-treatment of the substrate with 100% helium and 99% helium/1% oxygen plasmas showed upto a 50% increase in the force required to peel off the nanofiber layer. This force was further increased upto 75% after pre- as well as post-plasma treatment of the composite bandages. Plasma pre-treatment ofthe gauze fabric prior to nanofiber deposition and post-treatment to the composite bandages significantlyreduced degradation of the nanofiber layer during repetitive flexing. Air permeability and moisture vaportransport were significantly reduced due to the presence of a nanofiber layer upon the substrate. Theresults of surface elemental analysis showed that the adhesion and durability increase are mainly due tothe active species generated by plasma on the surface of cotton substrate as well as on the surface of thesilk fibroin nanofibers.
Keywords: Wound Healing; Adhesion; Silk Fibroin; Nanofibers; Wound Dressings; Bandages; Atmospheric Pressure Plasma